Initial Experience of Contact Laser Vaporization of the Prostate (CVP) for Benign Prostate Hyperplasia Patients With Hemorrhagic Risk - Yushi Araki; Takashi Kawahara; Teppei Takeshima; Kazuhide Makiyama; Hiroji Uemura (Advances in Urology)
Conclusion: CVP treatment appears to be acceptable for BPH patients with hemorrhagic risk. In this study, late-onset hemorrhage occurred approximately 1 month postoperatively. Close postoperative follow-up is required.